Permittivity sensor development for lunar and planetary surface exploration - Gscheidle, Christian; Witzel, Thilo; Smolka, Alexander; Reiss, Philipp (Frontiers in Space Technologies, 2024)
Permittivity sensors measure the electric permittivity (formerly dielectric constant) of a sample between its electrodes and offer a reliable method to characterize the subsurface of planetary bodies in-situ. One potential application is the identification and mapping of water ice at the poles of the Moon. In this paper, the scientific background and heritage of the permittivity sensor concept is discussed, and the implemented electronic architecture is introduced focusing on the novel patch electrodes. The data processing approach for the measurements is based on Fourier transformation and numerical simulation setup are used for performance predictions.The calibration of the sensor validates the functionality of the electronics, and results from both simulations and characterization experiments show that the concept is applicable in the exploration scenario. Considering both engineering and scientific aspects, the results highlight the permittivity sensor's suitability for lunar and planetary exploration missions, albeit further points for improvement are identified.